Marketing: Events as marketing tools in Thai Hospitality Industry - Hu, Wenzhuo (2012)
Thailand is a developing country in Southeast Asia. It is one of the top tourist destinations in the world. The tourism industry has a big impact on this country’s economy, largely from foreign tourism. Tourism Authority Thailand as a marketing tool promotes Tai tourism industry and as a new concept to develop policy and marketing plan in tourism market in Thailand. However, the most of previous studies just have focused on foreigner travel in Thailand but only a few studies mentioned Thailand as a Thai tourism destination to affect Thai hospitality industry. Therefore, this dissertation will investigate some hotels in Thailand by event marketing tools and also will research how Thai small to medium sized hotels use experiential event marketing skills to stimulate their business and Tai hospitality industry.